EKSISTENSI MADZHAB DALAM HUKUM ISLAM MASA KONTEMPORER - M Saleh (Istinbath : Jurnal Hukum, 2016)
Based on the above explanation can we understand that differences of opinion among Muslims is not a new phenomenon, but since most early Islamic period of dissent that has already happened. The difference occurs based and the existence of different views of each sect in understanding Islam the truth on that one. For that we Muslims should always be open and arif in memendang as well as understand the meaning of the difference, up to a point the conclusion that is different it's not identical to the contrary during the difference it move towards truth and Islam are one in diversity. Khilafiah problem is the problems that occur in the reality of human life. Among the problems the khilafiah anyone solve it in a way that is simple and easy, since there is a mutual understanding based on common sense. But behind that khilafiah can be a problem stand to establish harmony among Muslims because of the attitude of the taasub (fanatical) excessive, not based on considerations of common sense and so on. Dissent in the Court of law as a result of research (ijtihad), need not be seen as a factor that weakens the position of Islamic law, even on the contrary can provide respite. This means, that people are free to choose one of the opinion of the many, and not just glued to one opinion only. Therefore, the existence of bermadzhab in Islamic law in contemporary era is still required to align clients ' factual truth of the Qur'an and as-Sunnah.